2013
DOI: 10.1002/smll.201203200
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of the Structure of Pt–Cu Alloy Nanocrystals by Glycine‐Mediated Sequential Reduction Kinetics

Abstract: Uniform Pt-Cu alloy nanocrystals in the shape of dendrite, yolk-cage, and box structures are prepared via a facile wet-chemical reduction route in which glycine is demonstrated to alter the reduction kinetics of metal cations, critical to the morphology of the obtained product. These alloy nanocrystals exhibit superior specific activity and stability in the electro-oxidation of methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 32 publications
3
90
0
Order By: Relevance
“…PVP was found out to act as stabilizing agent to protect the concaved nanocubes and glycine was evidenced to stabilize the high index facets. When CuCl 2 was introduced into the system, branched and yolk-shell structures were formed 28 . The mechanism study revealed that glycine showed stronger binding with Pt 4+ than Cu 2+ , resulting in faster reducing of Cu than Pt, then the galvanic etching of Cu by Pt lead to hollow structures.…”
Section: Several Intricate Pt-cu Alloy Architectures Have Been Synthementioning
confidence: 99%
See 1 more Smart Citation
“…PVP was found out to act as stabilizing agent to protect the concaved nanocubes and glycine was evidenced to stabilize the high index facets. When CuCl 2 was introduced into the system, branched and yolk-shell structures were formed 28 . The mechanism study revealed that glycine showed stronger binding with Pt 4+ than Cu 2+ , resulting in faster reducing of Cu than Pt, then the galvanic etching of Cu by Pt lead to hollow structures.…”
Section: Several Intricate Pt-cu Alloy Architectures Have Been Synthementioning
confidence: 99%
“…S12c, d). The amino acid was found to coordinate with metal precursors at the beginning of the reaction, thus influence their reducing speed 28 . On the other hand, the amino acids are able to bind at the surface of metal particles 24 , consequently their growth kinetics and morphologies would be influenced 30 .…”
Section: Several Intricate Pt-cu Alloy Architectures Have Been Synthementioning
confidence: 99%
“…The properties of noble metal nanocrystals depend highly on their composition and shape [6][7][8]. Pt-based nanocrystals are the most significant electrocatalysts for the reactions of oxygen reduction and small organic molecule oxidation in fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…After cooling, the products were separated by centrifugation at 15 000 rpm for 15 min, washed several times with water by sonic cleaning, and then dried at 60 o C for 10 h in a vacuum dryer. Finally, the Pd-NWNWs were treated with UV irradiation (wavelength at 185 and 254 nm in air) for 5 h to remove the PVP and EDTA before electrochemical testing [31][32][33][34].…”
Section: Preparation Of Pd Nanowire Network (Pd-nwnws)mentioning
confidence: 99%